Tailoring the photoluminescent and electrical properties of tin-doped ZnS@PVP polymeric composite films for LEDs applications - Badawi, Ali; Alharthi, Sami S. (Superlattices and microstructures, 2021)
In the present work, tailoring the photoluminescent and electrical properties of Zn1-xSnxS@PVP polymeric composite films has been achieved for LEDs applications. Un-doped and 1.0 wt % of Sn-doped ZnS in polyvinyl pyrrolidine (Zn1-xSnxS@PVP) polymeric composite films were prepared using solution casting technique. The effect of Sn molar ratio x (x: 0 to 0.3) on the morphological, structural, photoluminescent and electrical properties is explored using a scanning electron microscope, X-ray diffraction (XRD), photoluminescence (PL) and DC electrical conductivity studies. XRD measurements reveal the amorphous nature of both bare PVP and Zn1-xSnxS@PVP polymeric composite films. The PL spectra measurements of the prepared films exhibit broad emission peaks with maxima intensities ranged from 400 to 417 nm. The Gaussian fitting method is used to de-convolute the PL emission bands of bare PVP and Zn1-xSnxS@PVP polymeric composite films. Three emission peaks for ZnS@PVP polymeric film are noticed at 392, 430 and 476 nm. An extra emission peak located at the green light region (480–502 nm) is observed for Zn1-xSnxS@PVP composite films. The electrical conductivity of the prepared Zn1-xSnxS@PVP polymeric composite films is enhanced thirty times more than that of bare PVP one. The prepared Zn1-xSnxS@PVP polymeric composite films could play an important role in LEDs applications. [Display omitted] •Tailoring the photoluminescent properties of Zn1-xSnxS@PVP have been investigated for LEDs applications.•XRD measurements reveal the amorphous nature of the prepared polymeric composite films.•Three emission peaks for ZnS@PVP polymeric film are noticed.•An extra emission peak located at 480–502 nm is observed for Zn1-xSnxS@PVP films.•The dc-electrical conductivity of Zn1-xSnxS@PVP polymeric composite films is enhanced.